Antibacterial activity of Caesalpinia spinosa (tara) on Porphyromonas gingivalis - Montenegro Chipana, Alex (2016)
Objective: Determine the antibacterial activity in vitro of five concentrations (6.25, 12.5, 25, 50 and 75 mg / mL) of the alcoholic extract of Caesalpinia spinosa “tara” (EACS) on Porphyromonas gingivalis. Materials and method: The study is experimental, prospective, comparative in vitro and kind, was carried out in the Laboratory of Microbiology, Faculty of Dentistry, San Marcos. Diffusion method was used in plate solutions to confront the alcoholic extract of Caesalpinia spinosa and compared with the positive control chlorhexidine 0.12% and Alcohol 96 º negative control. Results: It was found that the concen-tration of the alcoholic extract of Caesalpinia spinosa has antibacterial effect on Porphyromonas gingivalis, although the increased concentration bears no proportion to the increased diameter of the inhibition zone. Statistical analysis using the Kruskal-Wallis test found no significant differences between different concentrations of EACS and by the Mann - Whitney determined that there are no significant differences between the EACS and the positive control chlorhexidine 0.12% and control Alcohol 96 ° negative. Conclusions: We have demonstrated the antibacterial effect on Porphyromonas gingivalis.